Mulheres, ecofeminismo e direito dos desastres: raízes que anunciam resistências - Roso, Bianca Larissa Soares de Jesus (2021)
The challenges and obstacles faced by women and their potential in environmental disasters, in addition to the ecological and planetary crisis, have made the environment and women, since 1970, the agenda of activists and researchers. The fact is that women are impacted differently in this context. Mainly because of the different attribution of responsibilities and their unfavorable position in the hierarchies of patriarchal society. Hence the importance of researching gender related to Disaster Law, aiming at emancipatory perspectives to halt social setbacks and oppression. After all: how do environmental disasters affect the lives and rights of the women affected? How can the Ecofeminist view assist in their understanding, prevention, and reparation? To answer these questions, we started by analyzing the case involving the bursting of the chemical tailings dam in Mariana (MG) in 2015. The methodology and strategy of action in this research followed the trinomial: basic theory, procedure and technique. Thus, based on the Ecofeminist theory, a pragmatic-systemic approach was used, conferring the fusion between Law and various systems such as: politics, history, culture and ecology. As a procedure method the bibliographical and documental analysis was used, as well as semi-structured and non-directive interviews with the members of the Working Group (Grupo Interdefensorial do Rio Doce - GIRD), with the purpose of ascertaining the facts, opinions and conducts in the Mariana case (MG). The technical instrumentalization was developed by means of the production of tables, summaries, fiches, as well as data convergence and analysis. At the end of the research, we noticed a lack or even inexistence of terminology that could be used by women affected by disasters. This lack of terminology is necessary because women are, in fact, among the most vulnerable groups of the affected population. It is even possible to identify patterns of impacts suffered by women as a result of environmental disasters. In this sense, combining Ecofeminism with Disaster Law can help refound the legal form currently given to its treatment. By giving a generified vision to the populations affected by disasters, it is possible to reinforce structures that, when articulated, will form a solid legal basis for the protection and realization of an expanded dignity.